Pengaruh Kepercayaan Merek, Kepuasan Merek, dan Kepribadian Merek Terhadap Loyalitas Pada Gen Z di Boyolali - Maulidya, Ikka; Walyoto, Sri (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This study was conducted to determine the effect of brand trust, brand satisfaction, and brand personality on brand loyalty for Vaseline hand & body lotion products among Generation Z in Boyolali. This research uses quantitative methods, with purposive sampling techniques. The sample in this study amounted to 152 respondents, namely Generation Z users of Vaseline hand & body lotion products in the Boyolali area and who have made purchases two or more. The types of data used are primary and secondary data. The questionnaire distribution was carried out online and offline. The data was analyzed using the SPSS 21.0 program using multiple linear regression data analysis techniques. The results of this study indicate that brand satisfaction and brand personality have a significant positive effect on brand loyalty. While brand trust has a negative and insignificant effect on brand loyalty. Of the three variables, there is one variable that has a negative and insignificant effect on brand loyalty, therefore it can be a concern for the Company to be able to increase brand trust to influence the brand loyalty of Vaseline hand & body lotion products.